JAMAL’S ENDEAVOR AGAINST THE DEMANDING LIFE IN DANNY BOYLE’S SLUMDOG MILLIONAIRE MOVIE (2008): AN INDIVIDUAL PSYCHOLOGICAL PERSPECTIVE - INDRAWATI, RENY (2011)
This study describes the endeavor of Jamal against the demanding life view from individual psychological perspective, and analyzes the movie “Slumdog Millionaire” based on its structural elements. The research is conducted by using qualitative method. In this method, the researcher uses two data sources, namely primary and secondary data sources. The primary data source is film Slumdog Millionaire directed by Danny Boyle. The secondary data source are the books about individual psychology and the other sources, which are related to the analysis. The method of collecting data is observation and library review. Based on the analysis, the study reveals that there are some motives underlying the endeavor of Jamal Malik. Fiction finalism deals with Jamal’s expectation of his goals of life motivate him to make a great effort. Inferiority feeling of Jamal that appears every time makes him change his behavior to strive harder to accomplish his superiority. Striving for superiority motivates him to faces all problem and gets his dreams as proper as possible. Jamal’s style of life makes him become a useful type of person. His social interest motivates him to communicate and cooperate with others in order help himself or people surrounding him. His creative power motives him to have plans to reach his goal or solutions of his problem.